Development of Interactive Animation Video Media in Arabic Language Learning for Class X MA Al-Kenaniyah Students, East Jakarta - Fatkhur Roji (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
The research conducted by the researcher is related to the development of interactive video-based Arabic language learning media. The objectives of this study are (1) to find out how interactive video-based Arabic language learning media can be developed, and (2) to find out whether interactive video-based Arabic language learning media is effective. Of course, the benefits of this study for educators and teachers are to assist in the creation and development of interactive video-based learning media to provide and present practical and effective teaching materials. This type of research uses the type of research and development (R&D) using the research and development (R&D) approach. The R&D research approach is a process used to develop and validate educational products. This study discusses the ADDIE development model which consists of five stages. The main formats are analysis, design, development, implementation, and evaluation. Field trials were conducted at the implementation stage of the product development program. In this case, students of class X MA Al-Kenaniyah became the subjects of the study. The results of the study showed that the animated video-based Arabic language learning media product had been tested, assessed and verified by experts in their respective fields. The validation value set by the material expert was 47 with very valid validity criteria. The validation value set by media experts is 60 and the validity criteria are very appropriate.